Amido functional phthalocyanines as metal ion sensor; synthesis, characterization, spectroscopy, electrochemistry, in-situ spectroelectrochemistry - KOCA, ATIF (ELSEVIER SCIENCE SA, 2011)
Tetrasubstituted metal ion sensor amido functional phthalocyanines, PyMA-MPc, {PyMA: [N-1,N-3-bis(pyridin-2-ylmethyl)malonamide], M = Pd(II), Cu(II) and Co(II)} bearing amido functionality on the periphery were synthesized from the corresponding tetrasubstituted diethylmalonate substituted phthalocyanines, DEM-MPc (DEM: diethylmalonate; M = Pd(II), Cu(II) and Co(II)), and 2-aminopyridine in N,N-dimethylaminoethanol (DMAE) solvent. The new complexes have been characterized by elemental analysis, FT-IR, H-1 NMR and mass spectra. Peripheral malonamide groups of the phthalocyanine complexes serve as exocyclic binding sites for metal ion, such as Pd-II and also increase the solubility in protic solvents, i.e MeOH. Protonation of the pyridyl groups with HCl formed quaternized salts of the MPc, N-1, N-3-bis(pyridin-2-ylmethyl) malonamide substituted metallophthalocyanines (PyMA-PdPcx8HCl) which are freely soluble in aqueous media. Methylation of M[ Pc(CH(COOC2H5)(2))(4)] with CH3I gave the octacationic 2(3), 9(10), 16(17), 23(24)-tetrakis-[N-1,N-3-bis(N-methylpyridin-2-ylmethyl)malonamide]-phthlocyaninato Cu(II) salts which are freely soluble in water. Voltammetric and spectroelectrochemical studies show that while PyMA-Pd(II) Pc and PyMA-Cu(II) Pc give ring-based reversible/quasi-reversible redox processes, PyMA-Co(II) Pc give both metal and ring-based, reversible/quasi-reversible electron transfer processes. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: Phthalocyanines; Water-soluble; Malonamide; Aggregation; Electrochemistry; Spectroelectrochemistry; PORPHYRAZINES; MACROCYCLES; COMPLEXES; METALLOPHTHALOCYANINES; SUBSTITUENTS; BINDING; FILMS